Penerapan Model Pembelajaran Outentic Learning Untuk Meningkatkan Hasil Belajar IPA - Simangunsong, Rugun (JURNAL GLOBAL EDUKASI, 2017)
Abstract: The purpose of this research is to improve science learning outcomes by applying Outentic Learning learning model on Organ and Human Animal Body material. Subjects in this study were students of grade V SD Negeri 014691 Serdang district Meranti academic year 2016/2017. The results obtained by the learning process after the research apply the Outentic Learning model to improve the learning outcomes of Natural and Organ Veterinary Science materials reaches an average value of 77.2 in cycle I after motivated in cycle II the average score reaches 84.8 means there is an increase of 7.6. Completeness of learning outcomes in the first cycle reached an average value of 74.7% after reflection and recommendation in cycle II reached 88% means there is an increase of 11.3%. It can be concluded that the application of Outentic Learning learning model can improve the learning outcomes of science on human and animal organ materials in grade V students SDN 014691 Serdang district Meranti academic year 2016/2017. Keywords: Outentic Learning, organs Abstrak: Tujuan penelitian ini adalah untuk meningkatkan hasil belajar IPA dengan menerapkan model pembelajaran Outentic Learning pada materi Organ Tubuh Manusia dan Hewan. Subjek dalam penelitian ini adalah siswa kelas V SDN 014691 Serdang kec. Meranti tahun pelajaran 2016/2017. Hasil penelitian diperoleh hasil proses belajar setelah penelitian menerapkan model Outentic Learning untuk meningkatkan hasil belajar IPA materi Organ Tubuh Manusia dan Hewan mencapai nilai rata-rata 77,2 pada siklus I setelah termotivasi pada siklus II nilai rata-rata mencapai 84,8 berarti ada peningkatan sebesar 7,6. Ketuntasan hasil belajar pada siklus I mencapai nilai rata-rata 74,7% setelah refleksi dan rekomendasi pada siklus II mencapai 88% berarti ada peningkatan sebesar 11,3%. Dapat disimpulkan penerapan model pembelajaran Outentic Learning dapat meningkatkan hasil belajar IPA pada materi organ tubuh manusia dan hewan pada siswa kelas V SDN 014691 Serdang kec. Meranti tahun pelajaran 2016/2017. Kata kunci: Outentic Learning, organ tubuh